Panchamahabhuta- Five Basic Elements and their Utility in Ayurveda: A Review - Palsra, Pankaj; Sharma, Shruti; Kumar, Ravinder; Thamman, Rakesh (International Research Journal of Ayurveda & Yoga, 2022)
There are various principles like Tri Dosha (Biomaterials), Sapt Dhatus (Tissues) and Tri Mala (waste products), Srotas, Agni, etc. mentioned in Ayurveda, but fundamental of all these is Panchmahabhuta principle. In Ayurveda it is stressed that both Chikitsa Purush (living human body) and Dravyas (Drugs) used for treatment of Chikitsa Purush, are made up of Panchmahabhuta. So, for any Vaidya (Physician) to achieve the ultimate aim of Ayurveda (to maintain health of healthy person and prevent him/her from diseases) it is very important to have deep and through understanding Panchmahabhuta concept. In this review article stress is given on clinical application of Panchmahabhuta principle in Ayurveda and focused on the inter relation of Panchmahabhuta with various other components of body like Tridosh, Dhatu, Mala, Triguna, Rasa etc.